COMPARATIVE ANALYSIS OF THE LEGAL INDEPENDENCE OF THE UNIVERSITIES OF EU MEMBER STATES (Law and world, 2015)
Based on the comparative analysis of the legal autonomy of the universities of the member States of EU, the ultimate aim of the article is the provision of a special status to the Tbilisi State University, taking into account its unique role in the development of education, science and culture in the history of Georgia.